PENGGUNAAN REDISET LQ-1106 PADA CAMPURAN ASPAL HRS-WC - Rikki Sofyan Rizal; Pratikto; Susilowati, Anni; Prasetyo, Rudolf Triamba; Tsaluji, Imron (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
Hot Rolled Sheet-Wearing Course is a hot mix asphalt with the use of gap graded aggregate. The most important characteristics of this mixture are durability and flexibility, but this layer is also required to have sufficient stability to accept traffic loads acting directly on the layer. Therefore, an innovation is needed that can improve the stability properties of the asphalt mixture. In this study, the authors used the Rediset LQ-1106 additive as a solution in increasing the stability value of the asphalt mixture. The purpose of this study was to determine the characteristics of the HRS-WC asphalt mixture with the addition of Rediset LQ-1106 and determine the optimum percentage of Rediset LQ-1106 used. This research method consists of four stages, the first is to test the material properties. Second, determine the optimum asphalt content in the HRS-WC asphalt mixture. Third, perform Marshall test, with variations of Rediset LQ-1106 additive content of 0%; 1%; 2%, 3% and 4% of the optimum asphalt content. Fourth, discuss and conclude the results of the research that has been done. The results showed that the HRS-WC asphalt mixture had an optimum value of 7.4% asphalt content and 1.65% Reset LQ-1106. The results also show characteristics that meet the requirements of the 2018 Binamarga specification with a VMA value of 18.75%, VIM 5.40%, VFB 72%, stability of 1410 kg, flow 3.95 mm and an MQ value of 350 kg/mm.